Role of classification algorithms on brain mri data - MUKULIKA PANDA; SASHIKALA MISHRA; KAILASH SHAW; DEBAHUTI MISHRA (International Journal of Pharma and Bio Sciences, 2016)
Image classification is an important problem of computer vision. In the world of medical science everyday doctors are encountered with various types of image related problem. Pattern classification is a solution to categorize the images. In this paper we have considered the medical dataset like Brain Tumor.To select the appropriate features PCA has been used in the paper.The Otsu’s method is used to find a segmented image of brain MRI data where as for classification SVM with various kernel functions has been implemented and the result has been established in the manuscript.